AB0011 HLA-DP Polymorphisms Play Protective Role in Systemic Lupus Erythematosus in Chinese Han Population. (15th July 2016) - Junlong, Z.; Wenli, Z.; Anning, T.; Lin, C.; Bin, Y.; Lanlan, W.
Abstract : Background: With the application of Genome-Wide Association studies (GWAS), the SLE risk gene loci in HLA-DR and HLA-DQ are gradually revealed [1]. However, the association of HLA-DP polymorphisms with SLE is pretty few reported. Considering the variants in rs3077 and rs9277535 in HLA-DP region were estimated influenced the immune response by affecting antigen presentation of HLA class II molecules to CD4+ T cells [2], it is worthy to explore the role of HLA-DP polymorphisms in SLE. Objectives: Exploring the effects of presently hot HLA-DP SNPs, rs3077 and rs9277525 on SLE. Methods: 335 SLE patients and 635 healthy controls were recruited in present study. Genotyping was performed with polymerase chain reaction-high resolution melting (PCR-HRM) assay and the data was analyzed using SPSS19.0. Results: A significantly positive correlation was observed between the SNP rs3077 and rs9277535 of HLA-DP and SLE susceptibility (rs3077, OR=0.74, 95%CI=0.60–0.91, P=0.004; rs9277535, OR=0.72, 95%CI=0.60–0.91, P=0.001). Moreover, in cytokines, there was significant positive association between rs3077 and IL-17 and INF-γ(P=0.037 and P=0.020 respectively; recessive model, P=0.011 and P=0.008, respectively) and the AA genotype predisposed to lower IL-17 and INF-γcompared with other two genotypes. However, none positive connection was found between rs3077 and IL-1 alpha, IL-4, IL-6, IL-10, and IL-23 (P=0.739, 0.624, 0.685, 0.887, and 0.937 correspondingly). None significant positive correlation could be observed between rs9277535 and any cytokines. Conclusions: HLA-DP polymorphisms (rs3077 and rs9277535) play a protective role in SLE susceptibility. And rs3077 play the role by affecting antigen presentation of HLA class II molecules for CD4+T cells and down-regulating the Th17 signal pathway. References: Ghodke-Puranik Y, et al. J Autoimmun. 2015; 64:125–136. Kamatani Y1, et al. Nat Genet 2009;41:591–595. Disclosure of Interest: None declared